2018
DOI: 10.3389/feart.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Paleointensity Study on the Holocene Surface Lavas on the Island of Hawaii Using the Tsunakawa–Shaw Method

Abstract: Investigating volcanic paleointensity during the Holocene is important for linking archeointensity and sedimentary paleointensity. Across the globe, the island of Hawaii is one of the most studied subaerial locations. Many published data from Hawaii are accessible in the paleointensity databases, but it is necessary to reassess these data because they were determined with experimental protocols not incorporating a modern test for multi-domain particles and with relatively loose selection criteria. To obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Because of this, we prefer to use f¯prob as a metric of how well a model performs as it allows for a few μT of uncertainty in the expected field value. Additionally, Yamamoto and Yamaoka (2018) suggested that the IZZI‐Thellier results for sites SW and TS may be biased slightly high due to acquisition of a thermo‐chemical remanent magnetization (TCRM), which is not detectable by our method. Yamamoto et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of this, we prefer to use f¯prob as a metric of how well a model performs as it allows for a few μT of uncertainty in the expected field value. Additionally, Yamamoto and Yamaoka (2018) suggested that the IZZI‐Thellier results for sites SW and TS may be biased slightly high due to acquisition of a thermo‐chemical remanent magnetization (TCRM), which is not detectable by our method. Yamamoto et al.…”
Section: Discussionmentioning
confidence: 98%
“…Because of this, we prefer to use prob f as a metric of how well a model performs as it allows for a few T of uncertainty in the expected field value. Additionally, Yamamoto and Yamaoka (2018) suggested that the IZZI-Thellier results for sites SW and TS may be biased slightly high due to acquisition of a thermo-chemical remanent magnetization (TCRM), which is not detectable by our method. Yamamoto et al (2003) also invoke a TCRM mechanism to explain the paleointensity overestimate for the Hawaii 1960 Flow, which is another of their sites for which we overestimate the expected intensity (see Figure 7 and Supplementary Data Set S1).…”
Section: Overly Precise Estimates Of B Ancmentioning
confidence: 97%
“…It is common practice to prolong the second hold duration to allow a similar amount of alteration to occur in a specimen that has presumably undergone some thermal stabilisation. Some examples of first (second) heat hold durations are: 30 (60) minutes (Tsunakawa and Shaw, 1994), 10 (20) minutes (Yamamoto et al, 2003), 24 (48) minutes (Yamamoto and Hoshi, 2008), 20-35 (30-45) minutes (Mochizuki et al, 2011), 15 (30) minutes (Yamamoto and Yamaoka, 2018), and 30 (40) minutes (Okayama et al, 2019).…”
Section: The Shaw Methodsmentioning
confidence: 99%
“…We adopted the following selection criteria, which are the same as those adopted in recent paleointensity studies using the Tsunakawa‐Shaw method (e.g., Ahn & Yamamoto, 2019; Kitahara et al., 2018; Yamamoto & Yamaoka, 2018).…”
Section: Methodsmentioning
confidence: 99%